Letter : Onteniente Hospital - Schevenels, Walther, b. 1894
042-0149-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, AVENUE D'ORSAY, PARIS-VIIe EXECUTIVE COMMITTEE : President: W.M. Citrine, Great Britain Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia General Secretary: W Schevenels TELEGRAMS : INTERFED-PARIS TELEPHONE : INVALIDES 45-88 AFFILIATED COUNTRIES : ARGENTINE BELGIUM CANADA CHINA CZECHOSLOVAKIA DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN HOLLAND HUNGARY INDIA LUXEMBURG MEXICO NEW ZEALAND NORWAY PALESTINE POLAND RUMANIA SPAIN SWEDEN SWITZERLAND UNITED STATES YUGOSLAVIA Sch/H Letter F.I. de Sol No. 539 4th May 1937. Mr. Walter M. Citrine, LONDON. Dear Comrade Citrine, ONTENIENTE HOSPITAL In reply to your letter of the 20th April under this heading, I would say that I have had a conversation on this point with our chief surgeon. Before taking any decision he would like to wait for a few days, in order to see what applications are coming in from other countries, and whether it is possible to engage Dr. Sligo as a surgeon and Mrs. Sligo as a nurse on the conditions mentioned in your letter and for the period up to 28th July. The question is only to avoid complications which might arise from a difference in treatment between the different surgeons, and it is for this reason that our chief surgeon would prefer to wait few days to see on what terms the other surgeons can be engaged, or, if the services of Dr. Sligo can be utilised, in what way the question of remuneration can be settled to meet his request. Yours sincerely W. Schevenels, General Secretary: 292/946/42/149